2022
DOI: 10.11591/ijere.v11i4.22688
|View full text |Cite
|
Sign up to set email alerts
|

Development of chemistry learners’ problem-solving skills through hands-on instructional model

Abstract: <p><span lang="EN-US">Learners can experience science in the real world by interacting with materials, collaborating with peers, and engaging in a problem-solving process. Notwithstanding, secondary school learners’ problem-solving skills (PSS) can be developed by using an instructional strategy that actively involves them in the learning process instead of sorely focusing on content learned. This paper shows how the production of materials for teaching and learning can go hand-in-hand with the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, a study by Jerrim et al (2022) found that there exists a relationship between learners' performance and their involvement in inquiry-based teaching and learning. By unpacking and applying this framework, science teachers are envisaged to develop an environment that fosters inquiry-based learning, enabling learners to actively engage in the scientific method (Ambarita et al, 2019;Kibga et al, 2022). This shift towards a more hands-on and analytical approach has the potential to enhance understanding, critical thinking, and problem-solving skills among learners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Jerrim et al (2022) found that there exists a relationship between learners' performance and their involvement in inquiry-based teaching and learning. By unpacking and applying this framework, science teachers are envisaged to develop an environment that fosters inquiry-based learning, enabling learners to actively engage in the scientific method (Ambarita et al, 2019;Kibga et al, 2022). This shift towards a more hands-on and analytical approach has the potential to enhance understanding, critical thinking, and problem-solving skills among learners.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a practicum serves as a valuable method to enhance students' cognitive abilities when studying physics [8][9][10]. In this process, students apply their observational findings from the practicum to bolster their existing theoretical knowledge, thereby constructing a robust conceptual framework [11][12][13][14]. The significance of engaging in practicum activities in the context of science education is underpinned by four pivotal reasons [15].…”
Section: Introductionmentioning
confidence: 99%